El genio de la raza - Javier Moreno Luzón (Mélanges de la Casa de Velázquez)
This article focuses on the transnational nature of two Cervantes’ centennials: that of the publication of Don Quijote de la Mancha, in 1905; and that of the death of its author, in 1916. Both of them became the symbols of Spanishness and the Hispanic word, so these celebrations helped to build a Spanish identity based on language and culture, an ethnic international community called la raza (the race), and some national identities linked to it throughout Latin America. Many countries organized similar commemorations where transnational forces have played a leading role, as have Spanish intellectual networks and migrant communities. The article goes into more detail on two cases: Cuba, where Cervantes’ admirers are divided between hispanophiles and hispanophobes; and Spain, where commemoration initiatives depend on American collaborations and where Spanish nationalism is subordinated to this foreign aid.